Research on the Boundary Element Method Algorithm of Capacitance Matrix of Wire Cable with Open Boundary - Niu, Mengyuan; Hu, Yusheng; Guo, Chouwei; He, Lijin (2023 International Conference on Microwave and Millimeter Wave Technology (ICMMT), 2023)
The boundary element method (BEM) for extracting the capacitance matrix of wire cable especially the processing of open boundary are studied. Two boundary conditions are analyzed, one is the first type boundary condition in which zero potential is applied on the truncation boundary, and the other is imposing a third type boundary condition on truncation boundary. In addition, the influence of the number of discrete elements of the open boundary on the calculation accuracy is also studied. The results show that the distance of the truncated open boundary from the model should be far enough to ensure the high solution accuracy, whether the first type or third type boundary condition is selected, while the discrete element number of open boundary elements has little effect on the solution accuracy, only several elements are needed. The obtained conclusions are important for improving the calculating accuracy and helpful to save computer memory.